Another Student Revolution? - Altbach, Philip; Luescher, Thierry (International Higher Education, 2020)
A wave of student activism is sweeping the world. Countries and regions such as Algeria, Bolivia, Britain, Catalonia, Chile, Ecuador, France, Guinea, Haiti, Honduras, Hong Kong, Iraq, Kazakhstan, and Lebanon, among others, have experienced campus activist movements, some of which have toppled governments. The reasons and results of these movements are varied, but most are related to social inequalities.